Pengenalan dan pelatihan membatik sebagai upaya menumbuhkan keterampilan dan melestarikan budaya pada mahasiswa Dayak di prodi pendidikan luar sekolah - Endah Yusma Pratiwi; Nur Mahmudah Rojabi (STAI Auliaurrasyidin Tembilahan, 2026)
Batik is one of Indonesia’s cultural heritages that needs to be preserved through the active involvement of younger generations. To date, Dayak students in the Prodi Pendidikan Luar Sekolah have rarely worn batik featuring traditional motifs from Central Kalimantan, indicating the need for a Community Service Program addressing this issue. This program aimed to develop batik-making skills and enhance awareness of cultural preservation among Dayak students in the Prodi Pendidikan Luar Sekolah. The implementation method consisted of material presentation, introduction to tools and materials, demonstration of batik-making techniques, hands-on practice, and activity evaluation. The results showed that participants experienced increased knowledge regarding batik motifs, philosophical meanings, basic batik-making techniques, and the importance of cultural preservation. In addition, participants acquired practical batik-making skills, including motif design, wax application (canting), coloring, and finishing processes. Therefore, the introduction and batik training activities can serve as an effective approach to developing skills while strengthening cultural awareness among students in the Prodi Pendidikan Luar Sekolah.